“Comparative evaluation of intranasal dexmedetomidine and intranasal midazolam for premedication in children undergoing anesthesia”: A 1-year double-blind randomized controlled trial - Narendra Malineni; Manjunath C Patil (Indian Journal of Health Sciences and Biomedical Research KLEU, 2017)
Introduction: Children undergoing surgical procedures can experience significant anxiety and distress during perioperative period. Use of sedative premedication helps to reduce anxiety and facilitate a smooth induction of anesthesia. Midazolam is the most commonly used premedication agent with adverse effects such as behavioral changes, hiccups, and paradoxical hyperactive reactions. Dexmedetomidine, a highly selective α-2 agonist, has sedative properties. Aims and Objectives: The aim and objective of this study was to compare the efficacy of intranasal dexmedetomidine and intranasal midazolam for premedication in pediatric age group for parental separation anxiety and acceptance of anesthesia mask. Materials and Methods: This study included 60 American Society of Anesthesiologists I–II patients aged 1–10 years undergoing lower abdominal and lower limb surgeries under caudal epidural anesthesia. Ethical committee's clearance and informed consent were obtained. Patients were allocated into two groups by a computer-generated randomization table to receive 0.2 mg/kg intranasal midazolam in Group M and 1 μg/kg dexmedetomidine in Group D intranasally using 1 ml tuberculin syringe. The Parental Separation Anxiety Scale (PSAS) and Mask Acceptance Scale (MAS) were assessed by an anesthesiologist blinded to the drug given. Heart rate and oxygen saturation were monitored till the end of the procedure. Results: Demographic data were comparable in both groups (P > 0.05). Mean PSAS was 1.2 ± 0.40 in dexmedetomidine group and 1.6 ± 0.56 in midazolam group (P = 0.003). Mean mask acceptance score (MAS) at the time of induction was 1.7 ± 0.59 in dexmedetomidine group and 2.1 ± 0.58 in midazolam group (P = 0.02). Conclusion: Intranasal dexmedetomidine 1 μg/kg is an effective alternative for premedication in children undergoing anesthesia and it results in better parent separation and better mask acceptance at the time of induction when compared to intranasal midazolam 0.2 mg/kg without much side effects or complications.